Modeling in vivo dynamics of RNA polymerase II meeting Nucleosomes - Abedini-Nassab, Roozbeh; Zhang, Xu (International Journal of Engineering and Technology, 2016)
Nucleosomes are shown to be barriers for RNA Polymerase II elongation along DNA, and their entry site behaves as the major obstacle. In this work, based on recent available in vivo data, we introduce a mathematical model for RNA Polymerase II reads. Moreover, as an alternative way, we use Radial Basis Function Network to predict RNA Polymerase II reads. Results of our models are in good agreement with experimental data. Furthermore, we introduce a random walk model which includes stalling, backtracking, and elongation phenomena. This model can predict and simulate the RNA Polymerase II trajectory on DNA, when it meets various nucleosomes.